4-[(4-Chlorophenyl)carbamoyl]butanoic Acid - Hanifa, B.; Sirajuddin, M.; Bari, A; Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (MDPI, 2021)
The X-ray crystal structure determination of the glutaric acid-amide derivative, 4-ClC6H4N(H)C(=O)(CH2)3C(=O)OH (1), is described. The backbone of the molecule adopts an extended, all-trans configuration but the terminal carboxylic acid and phenyl resides are twisted out of the plane through the bridging atoms, as seen in the torsion angles of O(carboxylic acid)–C(m)–C(m)–C(m) [13.9(5)°] and C(m)–N–C(p)–C(p) [47.1(4)°]; m = methylene and p = phenyl. The most striking feature of the molecular packing is the formation of supramolecular tapes mediated by carboxylic acid-O–H⋯O(carbonyl) and amide-N–H⋯O(amide) hydrogen bonding